2003
DOI: 10.1021/cm031061+
|View full text |Cite
|
Sign up to set email alerts
|

17O MAS NMR Study of the Bonding Mode of Phosphonate Coupling Molecules in a Titanium Oxo-Alkoxo-Phosphonate and in Titania-Based Hybrid Materials

Abstract: 17O-enriched phenylphosphonic acid (PhP*O3H2) was prepared from phosphonic acid dichloride and enriched water. This enriched phosphonic acid was used to prepare the titanium oxo-alkoxo-phosphonate Ti4(μ3-*O)(μ2-OPri)3(OPri)5(PhP*O3)3 (1) as a model compound, and titanium oxide/phenylphosphonate hybrids either by sol−gel processing with Ti(OPri)4 or by surface modification of a titania support. For comparison a gel sample was prepared using nonenriched PhPO3H2 and enriched water. The 17O MAS NMR spectra of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 46 publications
7
78
0
3
Order By: Relevance
“…Solid state NMR is an invaluable tool of investigation for such organophosphorus derived materials, giving a deep insight into chemical bonding. As an example, it has been shown recently [19] that 17 O parameters were extremely sensitive to the bonding mode of phosphonate molecules in hybrid solids. Here, we find a very good agreement between the experimental and calculated data for all nuclei ( 1 H, 13 C, 17 O, 31 P) of phenylphosphinic acid, confirming results dealing with a phosphonic derivative, C 6 H 5 PO(OH) 2 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Solid state NMR is an invaluable tool of investigation for such organophosphorus derived materials, giving a deep insight into chemical bonding. As an example, it has been shown recently [19] that 17 O parameters were extremely sensitive to the bonding mode of phosphonate molecules in hybrid solids. Here, we find a very good agreement between the experimental and calculated data for all nuclei ( 1 H, 13 C, 17 O, 31 P) of phenylphosphinic acid, confirming results dealing with a phosphonic derivative, C 6 H 5 PO(OH) 2 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The resonances around 28 ppm confirmed the presence of phosphonate units bonded to the surface. Previous studies on the surface modification of TiO 2 by phosphonic acids indicated that the main binding mode to the surface was tridentate (RP(OTi) 3 sites) [1,6,7]. The absence of a sharp resonance at 8 ppm showed that the formation of a layered titanium phosphonate phase by dissolution-precipitation process did not take place.…”
Section: Surface Modification Of Titania Particlesmentioning
confidence: 96%
“…Bonding to the surface involves the formation of M-O-P bonds, arising from the coordination of the phosphoryl oxygen to Lewis acid sites and the condensation of the P-OH groups with surface hydroxyl groups M-OH [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the natural abundance of 17 O is very low and the preparation of 17 O-enriched phosphonic acids is mandatory. 34) 3. Sol-gel chemistry of phosphonate-based hybrid materials…”
Section: )13)23)25)mentioning
confidence: 99%